PENGARUH TERAPI COGNITIVE REHABILITATION TERHADAP FUNGSI KOGNITIF PASIEN SKIZOFRENIA - Rita Untari; Feni Safitri (Universitas Muhammadiyah Klaten, 2023)
Schizophrenia is a severe mental disorder, organized into multiple dysfunctional domains including positive symptoms, negative symptoms, cognitive impairment, mood, carelessness, and aggression. Impaired cognitive function is an inability in attention, memory, consideration, problem solving, and the ability of executives such as planning, assessing, monitoring and evaluating. One of cognitive deficit therapy in schizophrenia is Cognitive Rehabilitation (CR) therapy. The purpose of this study is to determine whether there is an influence between cognitive therapy rehabilitation of cognitive function in schizophrenic patients. This research used Quasi Experiment with non-random pretest and posttest with control group design and method of data analysis used comparative test which is wilcoxon test and mann-whitney test. This research was done on schizophrenia patients in RSJD dr. Arif Zainudin Surakarta with 32 samples divided into control group (n = 15) and intervention group (n = 17). The cognitive function examination was assessed using the Montreal Cognitive Assessment (MoCA) version of Indonesia which has been validate. Interventions were done for during 6 sessions for 2 weeks and were done in groups. The cognitive function score in the control group, the pretest mean was 20.26 and the post-test mean was 21.60. For the function score in the intervention group, the average pretest score was 21.8, while the average post-test score was 25.6. The results of the research data analysis used the Wilcoxon test on the pretest and post-test of the control group with sig. 0.000 with a p-value <0.05; Wilcoxon test on pretest and post-test in the intervention group with sig. 0.000 with a p-value <0.05; Mann-Whitney test in the control-intervention group with sig. 000 with a p-value <0.05. This indicates that there is a significant difference in cognitive function abilities between the control group and the intervention group who underwent cognitive rehabilitation therapy for schizophrenia patients at RSJD Dr. Arif Zainudin Surakarta. This research shows a significant difference value between the control group and the intervention group. The result of the comparative test of both groups found that there was a significant effect on cognitive rehabilitation therapy on cognitive function in schizophrenic patients.